2009
DOI: 10.1080/07317110902895291
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Behavioral Assessment and Intervention in Residential Care: A Service Evaluation

Abstract: During the first 18 months after establishment of the Behaviour Assessment and Intervention Service (BAsIS), 31 clients living in Sydney Residential Aged Care Facilities were referred. Following comprehensive assessment, the BAsIS team recommended primarily psychosocial and environmental interventions that were case-specific and causality-focused. Behavioral observations and standardized measures of mood, behavior, and carer stress in relation to caring for the resident were collected at initial assessment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, the most useful interventions to effect change identify individual causes of BSC and suggest appropriate person-centred solutions. [68][69][70] This approach is reliant on staff having the required knowledge, skills and confidence to deliver person-centred care. The provision of person-centred support is an element of the common induction standards 71 for all social care workers in England.…”
Section: Person-centred Carementioning
confidence: 99%
“…Therefore, the most useful interventions to effect change identify individual causes of BSC and suggest appropriate person-centred solutions. [68][69][70] This approach is reliant on staff having the required knowledge, skills and confidence to deliver person-centred care. The provision of person-centred support is an element of the common induction standards 71 for all social care workers in England.…”
Section: Person-centred Carementioning
confidence: 99%
“…Behavior problems are prevalent among older adults (Brodaty et al, 2001;Snowdon, Miller, & Vaughan, 1996;Turner & Snowdon, 2009). An Australian report indicated that more than 90% of residents from a sample of 11 nursing homes manifested one or more challenging behaviors over the course of their dementia (Brodaty et al, 2001).…”
Section: The Clinical Contextmentioning
confidence: 99%
“…In the broadest context, challenging behavior denotes any behavior that is a barrier to a person participating in, and contributing to their community (including both active behaviors such as wandering, and passive behaviors such as withdrawal and inactivity); undermines, directly or indirectly, a person's rights, dignity or quality of life; and poses a risk to the health and safety of a person and those with whom they live and work. (McVilly, 2002, p. 7) An audit of the reasons for referral of 26 individuals to a behavior assessment and intervention service found that physical and verbal aggression were the most frequent reasons for referral, followed by disruptive vocalization, resistance to care, intrusiveness, and chronic psychotic behaviors (responding to auditory hallucinations, or acting on delusional beliefs; Turner & Snowdon, 2009). Other less frequent behaviors included crawling on the floor, sleep disturbance, overeating, hoarding, pacing, spitting, inappropriate urinating and defecating, and throwing colostomy bags.…”
Section: The Clinical Contextmentioning
confidence: 99%
“…Budgetary constraints affect the extent to which they can be available. A recent initiative in New South Wales, Australia (Turner and Snowdon, 2009), aims to educate staff of such facilities about prevention and treatment of mental disorders, while providing ongoing supervision and modeling of behavioral strategies. These Behavioral Assessment and Intervention Services (BAsIS) are linked to already existing old age psychiatry teams.…”
Section: U Lt I D I S C I P L I N a Ry T E A M Smentioning
confidence: 99%